2020
DOI: 10.1016/j.bbmt.2019.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Use and Increased Cancer Risk among Patients with Bronchiolitis Obliterans after Hematopoietic Cell Transplantation

Abstract: Azithromycin exposure during the early phase of allogeneic hematopoietic cell transplantation (HCT) has been associated with an increased incidence of hematologic relapse. We assessed the impact of azithromycin exposure on the occurrence of relapse or new subsequent neoplasm (SN) in patients with bronchiolitis obliterans syndrome (BOS) after HCT who are commonly treated with azithromycin alone or in combination with other agents. In a retrospective study of patients with BOS from 2 large allograft centers, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In the HCT population, long-term post-HCT azithromycin use has recently been associated with worse airflow decline-free survival and an increased risk for post-HCT hematologic malignancy relapse and secondary neoplasia, although it is unclear whether these findings were related to EDC activation or an off-target biological effect of azithromycin. [65][66][67] Ultimately, future studies are needed to determine whether the EDC can be selectively manipulated prior to HCT to amplify an adaptive response to chronic epithelial damage and prevent post-HCT lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the HCT population, long-term post-HCT azithromycin use has recently been associated with worse airflow decline-free survival and an increased risk for post-HCT hematologic malignancy relapse and secondary neoplasia, although it is unclear whether these findings were related to EDC activation or an off-target biological effect of azithromycin. [65][66][67] Ultimately, future studies are needed to determine whether the EDC can be selectively manipulated prior to HCT to amplify an adaptive response to chronic epithelial damage and prevent post-HCT lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…63 One of these agents, azithromycin, came under scru tiny due to increased relapse rates in a ran dom ized trial of azithromycin prior to HCT, 64 which were not con firmed in a larger study of azithromycin in established BOS, though a higher rate of sec ond ary neo plasms was observed. 65 At this time, the ben e fits of azithromycin likely out weigh the risks for most BOS patients, though ste roids and other risks for sec ond ary neo plasms should also be min i mized and per son al ized risks eval u ated. In patients with ongo ing pul mo nary decline, extra cor po real photopheresis may improve sur vival, which builds upon prior ret ro spec tive data of a response rate of approx i ma tely 60%.…”
Section: Bronchiolitis Obliterans Syn Dromementioning
confidence: 99%
“…The data for azithromycin alone are less robust [ 95 ]. While one study suggested that azithromycin alone as a preventive strategy for BOS may be linked to relapse, more recent larger studies did not show increased risk of relapse with azithromycin post-GVHD, although increased risk of secondary cancers with higher use of concomitant steroids was observed [ 96 , 97 ]. A combination of inhaled long-acting bronchodilator plus inhaled corticosteroid has been shown to improve FEV 1 at 1 month (by 200 mL and 12%) in newly diagnosed patients with mild-to-moderate BOS, without the use of systemic corticosteroids [ 98 ].…”
Section: Current Treatment Approachesmentioning
confidence: 99%